Solubilsasi Parasetamol Dengan Ryoto® Sugar Ester dan Propilenglikol - Deni Noviza; Nine Febrianti; Salman Umar (Fakultas Farmasi Universitas Andalas, 2015)
Paracetamol was an active ingredient, which is poorly soluble in water. Absorption of poorly soluble or slightly soluble in water is influenced by the rate of dissolution. Solubilization is an alternative to improve drug solubility in water with the addition of surfactant. The addition of Ryoto® sugar ester surfactant and propylene glycol cosolvent conducted to determine the concentration of Ryoto® sugar ester and prophylene glycol that increase the solubility and stability of the dosage form. Solubilization of Paracetamol with the addition of Ryoto® sugar ester without propylene glycol and combinations Ryoto® sugar ester and propylene glycol at a concentration below the CMC point (Critical Micell Concentration), at the point of CMC, and above the CMC points in a row is 0.005 mg/ml, 0.006 mg/ml, and 0.007 mg/ml with 10% propylene glycol. The highest solubility of Paracetamol achieved in the formula 7 with a combination of the addition Ryoto® sugar ester (0.007 mg/ml) and propylene glycol (10%) by the recovery percentage of 99.6%, and the combination is also obtained the best preparation stability which is not occur the color change in the preparations during storage at room temperature and place protected from direct sunlight for a month. The addition of Ryoto® sugar ester surfactant and propylene glycol increase the solubility and stability of the solubilization of Paracetamol preparations.